2023
DOI: 10.4007/annals.2023.197.1.5
|View full text |Cite
|
Sign up to set email alerts
|

On the Brumer--Stark conjecture

Abstract: In the setting of Brumer-Stark, ρ 1 is the trivial character and ρ 2 is a totally odd character χ. When p is odd, χ(c) = −1 ≡ 1 (mod p), where c denotes complex conjugation. Ribet's method therefore carries through. However when p = 2, we may have χ ≡ 1 (mod 2), and a new construction is necessary. This issue was handled in our paper [12], whose main theorem is a general version of Ribet's Lemma that applies in the residually indistinguishable case.The next issue at p = 2 concerns the Ritter-Weiss module ∇ Σ ′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(55 citation statements)
references
References 56 publications
1
54
0
Order By: Relevance
“…Let us stress however that the results in [10] still concern the dualized module Cl T,∨,− K and assume ETNC. Finally, Dasgupta and Kakde [4] proved the same formula on the Fitting ideal of Cl T,∨,− K without assuming ETNC. In a very recent paper [1], Atsuta and the second author determine the Fitting ideal of non-dualized T -smoothed class group Cl T,− K , still assuming the relevant instance of ETNC to hold.…”
Section: Motivation From Number Theorymentioning
confidence: 69%
See 1 more Smart Citation
“…Let us stress however that the results in [10] still concern the dualized module Cl T,∨,− K and assume ETNC. Finally, Dasgupta and Kakde [4] proved the same formula on the Fitting ideal of Cl T,∨,− K without assuming ETNC. In a very recent paper [1], Atsuta and the second author determine the Fitting ideal of non-dualized T -smoothed class group Cl T,− K , still assuming the relevant instance of ETNC to hold.…”
Section: Motivation From Number Theorymentioning
confidence: 69%
“…Before explaining our new notion of equivalence more closely, we quickly review the shape of known formulas for the Fitting ideals of arithmetic modules. In the previous work [4,6,10], etc., it is observed that the Fitting ideals of class groups can be described as a product θ J , where J is the so-called algebraic factor and θ is the analytic factor. Roughly speaking, this implies that the computation of the Fitting ideals of class groups splits up into determining the analytic factor θ , and the algebraic factor J , as two separate tasks.…”
Section: A New Notion Of Equivalencementioning
confidence: 99%
“…Note that these are all G-conjugate: σ(u A ) = u AAσ . The Brumer-Stark conjecture, proven up to powers of 2 in [DK23], implies that u e A , where e = #µ(H), gives an element of O H [1/p] × . More precisely, there exists an element ∈ O H [1/p] × such that ⊗ 1 = e • u and such H( e √ )/F is an abelian extension.…”
Section: Gross-stark Units and Stark-heegner Pointsmentioning
confidence: 99%
“…His conjecture related special values of derivatives of p-adic L-functions to local norms of Gross-Stark units, and was proved in [DDP11]. Recent work of Dasgupta and Kakde [DK23] on the Brumer-Stark conjecture refines this by removing the norm. The computation of Gross-Stark units over quadratic fields has been studied in [TY13] when p splits in F , and [Das07], [DK21], and [FL22] for p inert.…”
Section: Introductionmentioning
confidence: 97%
“…This unit has P-order equal to the value of a partial zeta function at 0 for a prime ideal P, of H, lying above p. The unit u is only non-trivial when F is totally real and H is totally complex containing a complex multiplication (CM) subfield, we assume this for the remainder of the paper. The ground-breaking work of Dasgupta-Kakde in [7] has shown that the Brumer-Stark conjecture holds away from 2.…”
Section: Introductionmentioning
confidence: 99%